Strong Core Theorems with Nonconvex Preferences - Anderson, Robert M. (Econometrica, 1985)
Examines the sequences of economies constructed by successive sampling from any characteristics of agents. In this paper author considers closeness of commodity bundles to demand sets, dependency of the agents bundles on convexity, relationship between core allocations and demand sets.